Kawan atau Lawan? Tuduhan Mata-mata Belanda pada Masa Revolusi 1945-1949 - Akbar, Allan (Masyarakat Sejarawan Indonesia, 2018)
The Indonesian Revolution period was a time with uncertainty as a result of the circulating information about social and political conditions in Indonesia were confusing. During that time, Dutch spy allegations between Indonesian people were flourished. One can easily be accused of being a Dutch spy only because there are attributes of the Dutch on his body, or even just he was dislike by the others. The Repubicans believe that the outbreak of Dutch spy allegations during that time came from NEFIS (Netherlands Forces Intelligence Service), the Dutch Intelligence Service, which actively engaged in propaganda and to create a tense atmosphere in Indonesia. This article will discuss the phenomenon of the spreading Dutch spy allegations among indigenous people and any social impact arising from these allegations.